2019
DOI: 10.2147/cmar.s209194
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of short-term and survival outcomes for transanal natural orifice specimen extraction with conventional mini-laparotomy after laparoscopic anterior resection for colorectal cancer</p>

Abstract: Background Transanal natural orifice specimen extraction (NOSE) in colorectal surgery has been introduced as a less invasive surgery. However, its long-term survival effects remain controversial. The aim of this study was to compare the short-term and long-term survival outcomes of transanal NOSE with those of the conventional laparoscopic approach with mini-laparotomy (LAP) for anastomosis construction and specimen extraction in sigmoid colon cancer or rectal cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…Postoperative pain on day 1 after surgery was lower in the TVSE group than the LAP group. Several studies [10,12,20] showed similar results. This reduction may be explained by the fact that minilaparotomy, which traumatizes the abdominal wall, is more likely to cause vessel and nerve injury and lead to increased postoperative somatic pain at the incisional sites [21].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Postoperative pain on day 1 after surgery was lower in the TVSE group than the LAP group. Several studies [10,12,20] showed similar results. This reduction may be explained by the fact that minilaparotomy, which traumatizes the abdominal wall, is more likely to cause vessel and nerve injury and lead to increased postoperative somatic pain at the incisional sites [21].…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies [10,12,19] demonstrated that patients who underwent laparoscopic anterior resection with TVSE for colorectal cancer benefited from shortterm outcomes, such as faster gastrointestinal recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous reports comparing laparoscopic NOSES with conventional laparoscopic surgery in colorectal surgery exist. Laparoscopic NOSES is safe and feasible with numerous advantages, including reduced pain and tissue trauma, fast recovery of intestinal function, and short postoperative hospital stay duration (19)(20)(21)(22)(23). Two meta-analyses involving 1,435 and 837 patients have also shown that compared with conventional laparoscopic surgery, NOSES may be a safe procedure that can significantly reduce the duration of hospital stay, accelerate postoperative recovery with improved cosmetic results, and in particular, minimize postoperative pain and complications while achieving similar oncological outcomes (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown [17][18] that adequate intestinal preparation before the operation and standard aseptic and tumour-free conditions during the operation can effectively avoid postoperative abdominal infections. Compared with conventional laparoscopic surgery, the probability of postoperative abdominal infections in patients treated with the NOSE technique does not increase significantly.…”
Section: Discussionmentioning
confidence: 99%